Genetic landscape of myelodysplastic syndrome and its prognostic relevance: a study from Pakistan - Waheed, Alia; Ahmed Khan, Saleem; Mahmood, Rafia; Saeed Malik, Hamid; Shafique Satti, Humayoon; Farid Khan, Fehmida (Journal of the Pakistan Medical Association, 2025)
Objective: To determine the genetic landscape of myelodysplastic syndrome patients, and to evaluate the impact of gene mutations on disease prognosis and overall survival. Method: This descriptive study was conducted from April 2019 to April 2021 at the Department of Haematology, Armed Forces Institute of Pathology, Rawalpindi, Pakistan, and comprised myelodysplastic syndrome patients of either gender. Targeted gene panel sequencing and Sanger sequencing were performed on blood and bone marrow samples. Different variant analysis was performed on sequencing data to identify the frequency of various mutations in genes related to myelodysplastic syndrome. Survival analysis and other tools were employed to analyse the impact of prognostic factors and gene mutations. Data was analysed using SPSS 24 and GraphPad Prism 8. Results: Of the 47 patients, 32(68.1%) were males and 15(31.9%) were females. The overall median age was 66 years (interquartile range: 20 years). Targeted gene panel sequencing was done in 09(19.14%) cases, and Sanger sequencing in 38(80.85%). Mutation was present in 15(32%) cases, while it was absent in 32(68%). The most commonly mutated genes were DDX10 (9%), TET2 (6%), RUNX1(6%), and ASXL1(6%). In general, presence of any gene mutation reflected a poor prognosis (HR=1.54, p=0.24) and shorter median overall survival (median OS=7.5 months, p-trend=0.07) in MDS patients. In individual patients harbouring these mutations, the DDX10 and TET2 mutations suggested a low-risk and favourable prognosis, while RUNX1 mutations had an adverse prognosis, translating into high-risk myelodysplastic syndrome. Whereas, the ASXL1 gene exhibited both low-risk and high-risk MDS disease. In addition, SF3B1 gene mutation in MDS-MLD-RS presented with a favourable outcome. Median overall survival was 11 months (ranging from 3-38 months with an IQR of 11 months), with 36(76.6%) patients succumbing to the disease. Conclusion: Involvement of genetic variants in the initiation, diagnosis and prognosis of myelodysplastic syndrome was noted. Key Words: Myelodysplastic syndromes, Exome sequencing, High-throughput nucleotide sequencing, Mutation, Survival rate.